Pengaruh Kompensasi dan Tunjangan terhadap Kepuasan Kerja Karyawan - Jusniwati Zai; Romana Rindra Nazara; Fajarman Lahagu; Irwan Nopian Sinaga (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to determine the effect of compensation and benefits on employee job satisfaction. Fair, adequate, and transparent compensation is considered a crucial factor influencing employee morale, loyalty, and retention. The study identifies seven key indicators to measure the impact of compensation on job satisfaction: salary adequacy, compensation fairness, punctuality of payments, compensation system transparency, incentives and bonuses, overall compensation satisfaction, and employee retention. The analysis results show that compensation has a significant influence on job satisfaction. Additionally, compensation effectiveness is affected by economic conditions, compensation system structure, and the relevance of compensation to employee needs. The study concludes that well-designed compensation can be a strategic tool for improving performance and reducing employee turnover.